Facilitating Transactions and Lawful Availability of Works of Authorship: Online Access to the Cultural Heritage and Extended Collective Licenses - Tryggvadóttir, Rán (The Columbia Journal of Law & the Arts, 2018)
The importance of providing access to the cultural heritage<a id="markerref-2295-1" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-1">1 is widely accepted. Digital technology has supplied powerful new tools to reproduce and disseminate works and at the same time has transformed the demands and expectations of end-users.<a id="markerref-2295-2" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-2">2 Nevertheless, there are several issues that cultural heritage institutions (“CHIs”) must resolve in order to maintain their role of preserving and disseminating cultural heritage in the digital age. Although some of those issues are budgetary rather than legal,<a id="markerref-2295-3" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-3">3copyright is obviously a key consideration in the digital use of in-copyright works by CHIs. The largest copyright challenge for CHIs is the process of identification of right holders of copyright and clearance of rights, i.e. obtaining authorization or licenses for use of in-copyright works. Stakeholders do not agree how best to facilitate CHIs in their important cultural role. Some advocate the establishment of legal exceptions whereas others favor licenses. My starting assumption is that, given the impact of online use, licensing is a more appropriate and flexible tool than exceptions. However, obtaining individual licenses for the use of in-copyright works held by CHIs is complicated, time-consuming, and costly, in particular for cross-border online use.<a id="markerref-2295-4" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-4">4 Thus individual licensing is not a practical solution for CHIs except for the use of a few well-defined works. Even collective licensing does not fully solve the licensing issue because no collective management organization (“CMO”) has mandates from all right holders in a given field.<a id="markerref-2295-5" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-5">5 Hence, I propose that the solution is to be found through collective licenses with legislative support, such as the system of extended collective licenses (“ECL”).<a id="markerref-2295-6" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-6">6 In this essay I will start by giving a brief account of the main strands which constitute an extended collective license in the Nordic countries, where it was first developed.<a id="markerref-2295-7" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-7">7 I will describe two examples where ECLs have been used to facilitate access to the cultural heritage, in Norway and Finland respectively. I will also discuss the compatibility of the system with international norms, in particular the Berne Convention,<a id="markerref-2295-8" href="https://lawandarts.org/article/facilitating-transactions-and-lawful-availability-of-works-of-authorship-online-access-to-the-cultural-heritage-and-extended-collective-licenses/#marker-2295-8">8 and finish with some reflections on challenges and benefits of the system of ECLs in facilitating access to cultural heritage.